Spectral, Conformational and Photochemical Analyses of Photochromic Dithienylethene: cis‐1, 2‐Dicyano‐1, 2‐bis(2, 4, 5‐trimethyl‐3‐thienyl)ethene Revisited. Issue 34 (9th October 2013) - Erko, Firealem G.; Berthet, Jérôme; Patra, Abhijit; Guillot, Régis; Nakatani, Keitaro; Métivier, Rémi; Delbaere, Stéphanie
Abstract: The conformational equilibrium and thermodynamic parameters of cis ‐1, 2‐dicyano‐1, 2‐bis(2, 4, 5‐trimethyl‐3‐thienyl)ethene (1a ) and its trans derivative1c are presented. Irradiation of both compounds was carried out by using 365 nm light, which affects the cis / trans isomerisation process, whereas irradiation with 405 nm light preferentially promotes the formation of the cyclised product. Prolonged irradiation of1a at 365 nm leads to the formation of a new derivative showing photochromic properties. Evidence for the formation of the novel derivative is presented, and details of its photochromic properties were investigated; a tentative mechanism has also been proposed. Abstract : The equilibrium between parallel and antiparallel forms of cis ‐ and trans ‐1, 2‐dicyano‐1, 2‐bis(2, 4, 5‐trimethyl‐3‐thienyl)ethene was studied by NMR spectroscopy. Photocyclisation or cis / trans isomerisation was induced by irradiation with 405 or 365 nm light. Extended irradiation of the cis compound generated two peroxy derivatives that thermally convert into a new coloured compound with its own photochromic properties.